My Body Is a Book of Rules - Washuta, Elissa (Book collections on Project MUSE., 2014)
As Elissa Washuta makes the transition from college kid to independent adult, she finds herself overwhelmed by the calamities piling up in her brain. When her mood-stabilizing medications aren't threatening her life, they're shoving her from depression to mania and back in the space of an hour. Her crisis of American Indian identity bleeds into other areas of self-doubt; mental illness, sexual trauma, ethnic identity, and independence become intertwined. Sifting through the scraps of her past in seventeen formally inventive chapters, Washuta aligns the strictures of her Catholic school education with Cosmopolitan's mandates for womanhood, views memories through the distorting lens of Law & Order: Special Victims Unit, and contrasts her bipolar highs and lows with those of Britney Spears and Kurt Cobain. Built on the bones of fundamental identity questions as contorted by a distressed brain, My Body Is a Book of Rules pulls no punches in its self-deprecating and ferocious look at human fallibility.